2016
DOI: 10.1056/nejmoa1514209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Avoidance on Peanut Allergy after Early Peanut Consumption

Abstract: Among children at high risk for allergy in whom peanuts had been introduced in the first year of life and continued until 5 years of age, a 12-month period of peanut avoidance was not associated with an increase in the prevalence of peanut allergy. Longer-term effects are not known. (Funded by the National Institute of Allergy and Infectious Diseases and others; LEAP-On ClinicalTrials.gov number, NCT01366846.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
269
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(287 citation statements)
references
References 16 publications
6
269
0
12
Order By: Relevance
“…We identified that IgE-mediated reactions constituted half of all documented adverse reactions to foods, with a report of anaphylaxis in 1 in 6 reactions. These findings support the pressing need for more food allergy evaluations, as well as a call for more allergists/immunologists, especially given new recommendations for early food introductions, less reliance on isolated positive test results, [35][36][37][38] and more aggressive use of OFC to diagnose food allergy. Last, our findings support that the EHR allergy module may be helpful in determining the epidemiology and risk factors for food allergy, as well as identifying patients for prospective clinical studies and/or food allergy evaluations.…”
Section: Discussionsupporting
confidence: 61%
“…We identified that IgE-mediated reactions constituted half of all documented adverse reactions to foods, with a report of anaphylaxis in 1 in 6 reactions. These findings support the pressing need for more food allergy evaluations, as well as a call for more allergists/immunologists, especially given new recommendations for early food introductions, less reliance on isolated positive test results, [35][36][37][38] and more aggressive use of OFC to diagnose food allergy. Last, our findings support that the EHR allergy module may be helpful in determining the epidemiology and risk factors for food allergy, as well as identifying patients for prospective clinical studies and/or food allergy evaluations.…”
Section: Discussionsupporting
confidence: 61%
“…The early introduction of peanut in a high-risk cohort (4-to 11-month-old children with severe atopic dermatitis and/or egg allergy and skin prick test (SPT) <4 mm to peanut) via integration of 6 g peanut three times a week into the diet resulted in an impressive reduction in peanut allergy after 60 months of therapy by 81.7% as compared to the avoidance group (19). Importantly, this effect persisted in the majority of the patients even after a prolonged avoidance period of 1 year (20).…”
Section: Tolerance Induction In the Prenatal/perinatal Periodmentioning
confidence: 99%
“…Recently, the LEAP study provided data for primary and secondary prevention of peanut allergy in a high-risk cohort (19,20), which will soon be reflected in new guidelines. Nevertheless, no therapies capable of restoring tolerance are available.…”
Section: Foxp3mentioning
confidence: 99%
“…Катамнез детей из исследования LEAP (Learning early about peanut allergy) показал, что в воз-расте 6 лет, после 12-месячного периода элимина-ции арахиса из рациона не наблюдалось увеличения частоты развития аллергических реакций на арахис в опытной группе [27,28]. В настоящее время на ос-новании данных, полученных от 10 международных педиатрических ассоциаций аллергологов, рекомен-дуется раннее введение арахиса детям из групп риска, но под контролем специалиста [29].…”
Section: оригинальные статьи в помощь практическому врачуunclassified